2019
DOI: 10.1177/0272431618824753
|View full text |Cite
|
Sign up to set email alerts
|

“Would You Be My Friend?”: Friendship Selection and Contagion Processes of Early Adolescents Who Experience Victimization

Abstract: Victimization in early adolescence can have severe negative consequences later in life. Friendships are especially important in this time period. The present study investigated friendship selection and influence (contagion) processes with regard to victimization, as well as prosocial and aggressive characteristics of victims’ friends. Using social network analyses (RSiena), we longitudinally analyzed data of five fourth-grade classrooms, including 185 students (56.8% girls; [Formula: see text] age at Time 1 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Selection and influence processes have been investigated with respect to victimization. Research in childhood generally does not find that friendships are based on similarity in victimization or that friends influence each other's level of victimization (Berger, Gremmen, Palacios, & Franco, 2019;, although one study found that defenders of victims in one school ran the risk of becoming victimized, thus, being "influenced" to take upon the role of victim (Huitsing et al, 2014). However, research in adolescence provides evidence for selection on the basis of general victimization (Lodder, Scholte, Cillessen, & Giletta, 2016), physical victimization (Sentse et al, 2013), or relational victimization (Sijtsema et al, 2013).…”
Section: Dynamics In Network and Bullying And Victimizationmentioning
confidence: 99%
“…Selection and influence processes have been investigated with respect to victimization. Research in childhood generally does not find that friendships are based on similarity in victimization or that friends influence each other's level of victimization (Berger, Gremmen, Palacios, & Franco, 2019;, although one study found that defenders of victims in one school ran the risk of becoming victimized, thus, being "influenced" to take upon the role of victim (Huitsing et al, 2014). However, research in adolescence provides evidence for selection on the basis of general victimization (Lodder, Scholte, Cillessen, & Giletta, 2016), physical victimization (Sentse et al, 2013), or relational victimization (Sijtsema et al, 2013).…”
Section: Dynamics In Network and Bullying And Victimizationmentioning
confidence: 99%
“…Therefore, classrooms are stable environments in which peer relationships unfold. Despite this particularity, research into adolescent peer relationships using Chilean samples has shown patterns similar to those found in American and European populations (Berger et al., 2015, 2019).…”
Section: Methodsmentioning
confidence: 94%
“…Victimized adolescents may be viewed as undesirable companions by their peers or offer little social status benefit to current or new friends (Ellis & Zarbatany, 2007;Sentse et al, 2013), making it difficult for them to keep friends over time (Sijtsema et al, 2013). Alternatively, victimized adolescents may strategically and proactively search for new friends (e.g., prosocial friends) or those with a different victimization status (Berger et al, 2019;Meter & Card, 2016). Increases in victims' friendship instability later in the school year could therefore be the natural consequence of searching for close friendships that may help mitigate continued peer victimization.…”
Section: Discussionmentioning
confidence: 99%